Pendampingan Pengelolaan Keuangan bagi Pelaku Usaha Mikro Kecil dan Menengah - Ardillah, Kenny (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve the understanding of Micro, Small, and Medium Enterprises (MSMEs) to be able to manage finances through transaction bookkeeping and preparing simple financial reports. The target of this PKM activity is MSMEs who sell online and are domiciled in Jabodetabek, the majority of whom are young people. The method of implementation of this PKM activity is training with the Presman and participatory methods. This PKM activity was carried out online for two days on October 12, 2024 and October 13, 2024. The results of this community service activity have been carried out well by achieving an average questionnaire score of 3.78 and an increase in pretest and posttest scores from 62 to 87. These results indicate an increase in understanding of MSMEs regarding transaction bookkeeping and preparing financial reports which are expected to help them in improving accuracy and competitiveness through accurate financial reporting.